Gestión de las rutas patrimoniales: “Rutas de la seda, Red viaria del Corredor Chang´an-Tianshan” en China y “Camino de Santiago” en Castilla y León = The Heritage routes management: “Silk Road: Chang´an-Tianshan Corridor” in China and “Camino de Santiago" in Castilla y León - Huo, Sija; Serrano, Enrique (Polígonos. Revista de Geografía, 2021)
La Unesco denomina a las rutas culturales definidas por su valoración histórica, patrimonial y territorial como “Rutas de patrimonio”. La concepción es distinta que la de los itinerarios culturales europeos y la solicitud para su declaración ha cambiado en el tiempo, promoviendo en la actualidad las solicitudes conjuntas entre varios países. Las rutas del Patrimonio Mundial implican una gestión y protección “lineal” y territorial, generando una protección similar a una red. Estos cambios en los alcances y contenidos de la protección elevan la importancia del estudio de los métodos de gestión y protección. El objetivo del trabajo es comparar dos rutas patrimoniales de la Unesco, para conocer los elementos comunes en la gestión y conservación y las diferencias estructurales, de gestión, uso y promoción territorial. Se estudian dos bienes inscritos como Patrimonio Mundial, el “Camino de Santiago de Compostela" en Castilla y León y la "Ruta de la Seda: red viaria del Corredor Chang’an-Tianshan" en China. Si las "Rutas de la Seda" sobresalen por la multiplicidad de culturas y paisajes con contenidos históricos y naturales diferenciados, el "Camino de Santiago" se caracteriza por la homogeneidad cultural y paisajística. Las dificultades de gestión se centran en la multiplicidad de leyes para los diferentes territorios, la aplicación de políticas conjuntas, la ausencia de consideración de la ruta como un todo y la orientación turística de las principales iniciativas públicas. Si el Camino de Santiago es una ruta patrimonial consolidada, la ruta de la Seda está en sus inicios como patrimonio lineal. The Unesco calls to the cultural routes defined by their historical, patrimonial and territorial value as "Heritage Routes". The idea is different from that of the European cultural itineraries and application for its declaration has changed over time. Currently joint requests between several countries is promoted. The routes of the World Heritage imply a "linear" and territorial management and protection, establishing a protection network. The changes on protection give importance to the study of management and protection methods. The aim of this work is to compare two heritage routes of Unesco, to highlight and to know the common elements in the management and conservation and differences on the structure, management, use and territorial promotion. Two World Heritage are studied, the "Camino de Santiago de Compostela" in Castilla y León and the "Silk Road: road network of the Chang'an-Tianshan Corridor" in China. If the "Silk Routes" stand out for the multiplicity of cultures and landscapes with differentiated historical and natural content, the "Camino de Santiago" is characterized by cultural and landscape homogeneity. The management and conservation as a single set, the multiplicity of laws for different territories, and the application of different policies with special emphasis on the heritage value of the landscape are also analyzed. Common management difficulties are centered on the multiplicity of laws for the different territories, the application of policies together, the lack of thoughtfulness of the route as a whole, and the tourist orientation of the main public initiatives. If the Camino de Santiago is a consolidated heritage route, the Silk Road is in its early days as a linear heritage.